(untitled) (Journal Of Educational and Psychological Researches, 2023)
The aim of the research is to find out the effect of the SPAWN strategy on the life skills of second-intermediate-grade students. This study stage represented the research community within the intermediate and secondary governmental daytime schools affiliated with the Directorate of Education of Diwaniyah. The experiment was applied in Al-Razai Intermediate School on a sample of second-grade intermediate students, including 66 students distributed into two groups: (32) students within the experimental group and (34) students within the control group. The two groups were equivalent with a number of variables (chronological age, intelligence test, previous information test, life skills scale). The results indicated that the two groups were equal in the mentioned variables. The researchers built a scale for a group of life skills consisting of (10) main skills and (50) sub-items, according to the theoretical definition of life skills and the classifications that were viewed, and after conducting the post-test of the scale on the research sample, the results showed there were statistically significant differences at level (0.05) in favor of the experimental group. In light of this, a set of recommendations and conclusions were drawn up including employing the SPAWN strategy in teaching chemistry. It is one of the active learning strategies and consists of five steps (absolute powers, problem-solving, alternative perspectives, what if? next).